Comparison of calculated lumbosacral epidural volumes of injectate using a dose regimen based on body weight versus length of the vertebral column in dogs. (January 2019) - Valverde, Alexander; Skelding, Alicia
Abstract: Objective: To compare volumes for epidural injection calculated on body weight or the length from sacrococcygeal space to occipital crest in dogs. Study design: Prospective study. Animals: A total of 431 dogs weighing mean ± standard deviation (range) 24.6 ± 16.1 (1.3–88.0) kg and with vertebral column length 67.6 ± 38.4 (24.8–119.4) cm. Methods: Dogs were separated into specific weight groups and body condition scores (BCS; 1–5): small (<10 kg), medium 10 to <25 kg), large (25 to <45 kg) and giant (≥45 kg). Calculations for a lumbosacral epidural dose were 0.2 mL kg −1 and for vertebral column length: 0.05 mL cm −1 (<50 cm), 0.07 mL cm –1 (50 to <70 cm), 0.08 mL cm –1 (70 to <80 cm), and 0.11 mL cm –1 (≥80 cm). A split plotanova ( p < 0.05) with weight, length and BCS as factors was used. Results: A significantly larger volume was calculated for length than for weight in small ( p < 0.0001–0.0003, BCS 2–5), medium ( p < 0.0001–0.0076, BCS 2–5), and large dogs ( p ≤ 0.0007–0.0019, BCS 2, 3). In large (BCS 4, 5) and giant dogs (BCS 2, 3), both calculated volumes were similar. In giant dogs (BCS 4, 5), a significantly smaller volume was calculated for length ( p ≤ 0.0002–0.0165). Regardless of BCS, small (2.18 versus 1.12), medium (3.99 versus 3.16), and large dogs (7.38 versus 6.82) had larger calculated volumes (mL) for length than for weight ( p < 0.0001), whereas giant dogs (10.04 versus 10.91) had smaller calculated volumes. Conclusions: and clinical relevance Mathematically, the epidural volume of injectate varies with the calculation method and is affected by BCS. Small and medium dogs have larger calculated volumes based on length than on weight, and this difference tends to disappear or revert as size increases.